Seven Winnings to Inclusion - Mahar, Patricia (Journal of the American Academy of Special Education Professionals, 2008)
This is a story about a fun and successful program that involved the integration of adults with developmental disabilities with adults without disabilities. Coach Mahar started the city’s first integrative softball team for players with and without disabilities. It is evident that the choices of recreational/leisure activities for adults with disabilities are still not available on a widespread basis. Too often, adults with developmental disabilities spend a great deal of time watching television and listening to the radio. Many adults with disabilities do not regularly participate in any recreational/leisure activities, especially community group activities.Mahar’s team was developed using the following guidelines: teaching the basics, developing self-advocacy skills and learning about accommodations and adaptations, getting to know each other, improving social skills and developing relationships with others, and growing personally. The team members with disabilities enjoyed a sense of belonging while those without disabilities experienced satisfaction in offering this opportunity.